2001
DOI: 10.1038/sj.onc.1204134
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of repression of squamous differentiation marker, SPRR1B, in malignant bronchial epithelial cells: role of critical TRE-sites and its transacting factors

Abstract: The overexpression of SPRR1B in bronchial epithelium is a marker for early metaplastic changes and the loss of its expression is associated with an irreversible malignant transformation. In the present study, we have used a model system consisting of normal and malignant bronchial epithelial (BE) cells to elucidate the dierential transcriptional control of SPRR1B. SPRR1B expression is either detectable or PMA (phorbol 13-myristate 12-acetate) -inducible in several malignant BE cells including squamous, adeno, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 36 publications
4
63
0
Order By: Relevance
“…The MYC oncogene, frequently overexpressed with or without amplification in lung cancers, is associated with a poor prognosis (Johnson et al, 1987), as is SERPINE1. (Robert et al, 1999) FOSL1 has been shown to play a role as a predominant component of the AP-1 complex in ras-induced transformation (Mechta et al, 1997), and it also mediates induction of SPRR1B in response to epithelial injury caused by a variety of carcinogens (Patterson et al, 2001;Vuong et al, 2002). Both COPB and ARCN1 constitute COPI-coated vesicles and are involved in the transport of G protein-coupled receptors, while the binding of Ras-related GTP-binding protein Cdc42 to another COPI subunit, COPG, has been shown to be important for transmitting transforming signals (Wu et al, 2000).…”
Section: Construction Of the Survival Prediction Models Specific For mentioning
confidence: 99%
“…The MYC oncogene, frequently overexpressed with or without amplification in lung cancers, is associated with a poor prognosis (Johnson et al, 1987), as is SERPINE1. (Robert et al, 1999) FOSL1 has been shown to play a role as a predominant component of the AP-1 complex in ras-induced transformation (Mechta et al, 1997), and it also mediates induction of SPRR1B in response to epithelial injury caused by a variety of carcinogens (Patterson et al, 2001;Vuong et al, 2002). Both COPB and ARCN1 constitute COPI-coated vesicles and are involved in the transport of G protein-coupled receptors, while the binding of Ras-related GTP-binding protein Cdc42 to another COPI subunit, COPG, has been shown to be important for transmitting transforming signals (Wu et al, 2000).…”
Section: Construction Of the Survival Prediction Models Specific For mentioning
confidence: 99%
“…For example, various toxicants and known carcinogens, such as tobacco smoke, silica and asbestos, persistently activate fra-1 but not fra-2 expression in lung cells (Reddy and Mossman, 2002). We have shown that FRA-1 upregulates the expression of genes associated with airway squamous cell metaplasia (Patterson et al, 2001) and that of matrix metalloproteinase-9, which is implicated in toxin-induced respiratory pathogenesis (Parks and Shapiro, 2001). Since an upregulation of FRA-1, rather than a mutational activation, contributes to the growth and proliferation of human tumors, it is important to understand its regulation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, FRA-1 is required for asbestos-induced mesothelial cell transformation (17). It up-regulates the expression of genes coding for airway squamous cell metaplastic marker (18), matrix metalloproteinase-9 (19), and CD44 and c-met proto-oncogene (20), which are implicated in toxin-induced respiratory pathogenesis. FRA-1 controls cell motility, invasion, and maintenance and progression of the transformed state in several cell types (for reviews, see Refs.…”
mentioning
confidence: 99%